1967
DOI: 10.1039/c19670000259
|View full text |Cite
|
Sign up to set email alerts
|

The structure of ginkgolide A, a novel diterpenoid trilactone

Abstract: GINKGOLIDE A is one of the bitter principles1 from and the X-ray analysis of a mono-p-bromo-Gingko biloba L., which is a gymnospermous tree and a single surviving species of the family Ginkgo-The aqueous extracts of the leaves were treated nceae, comprising Mesozoic plants. I n this Comwith charcoal, which absorbed bitter principles niuiiication we report the isolation of the three effectively. The collected charcoal was washed diterpenoids, their chemical and physical properties u-ith hot acetone. Concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…The structure of ginkgolide B (BN52021) has been determined by Dupont, Dideberg, Germain & Braquet (1986). A communication on the structure of the mono-p-bromobenzoate of ginkgolide A was published by Sakabe, Takada & Okabe (1967) but the atomic coordinates were not given. The final R value was 0.19 and a redetermination of the crystal structure of BN52020 is therefore necessary.…”
Section: 87(8)a and The O(3)-h(o3)o(2) Angle Is 130 (5) ° In Momentioning
confidence: 99%
“…The structure of ginkgolide B (BN52021) has been determined by Dupont, Dideberg, Germain & Braquet (1986). A communication on the structure of the mono-p-bromobenzoate of ginkgolide A was published by Sakabe, Takada & Okabe (1967) but the atomic coordinates were not given. The final R value was 0.19 and a redetermination of the crystal structure of BN52020 is therefore necessary.…”
Section: 87(8)a and The O(3)-h(o3)o(2) Angle Is 130 (5) ° In Momentioning
confidence: 99%
“…[69,70] The absolute configuration of ginkgolides was determined based on the octant rule analysis of 7-oxo-GC 10-monomethyl ether and another ketone derivative by Maruyama et al [59] Okabe and co-workers treated GA (1) with p-bromobenzoyl bromide to give prismatic crystals of 3-mono-p-bromobenzoate, which were submitted to crystallographic studies. [63] Initially, there was a discrepancy in the reported structures of GB (2) and GC (3) with respect to the relative stereochemistry of the hydroxy group at C1, as Maruyama et al concluded that the hydroxy group was in the a configuration, [59] whereas Okabe and co-workers suggested it to be in the b configuration. [62] Detailed NMR spectroscopic studies [71] and X-ray crystal structures of GB (2) and GC (3) [72,73] confirmed the a configuration of 1-OH.…”
Section: Structure Elucidationmentioning
confidence: 92%
“…[56][57][58][59][60][61] Independently, Okabe and co-workers determined the structures of GA (1), GB (2), and GC (3) from leaves of G. Biloba by means of X-ray crystallography. [62,63] Another ginkgolide, ginkgolide J (GJ; 4), was isolated from the leaves of G. biloba in 1987. [64] Interestingly, it appears that GJ (4) is only found in the leaves, whereas GM (5) is found only in the root bark.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…5661 Unabhängig davon bestimmten Okabe et al die Strukturen von GA ( 1 ), GB ( 2 ) und GC ( 3 ) aus Blättern von G. biloba durch Röntgenstrukturanalyse 62. 63 Ein weiteres Ginkgolid, Ginkgolid J (GJ, 4 ), wurde 1987 aus G.‐biloba ‐Blättern isoliert 64. Interessanterweise scheint GJ ( 4 ) ausschließlich in Blättern und GM ( 5 ) auschließlich in der Wurzelrinde vorzukommen.…”
Section: Isolierung Und Strukturaufklärungunclassified
“…Die absolute Konfiguration der Ginkgolide wurde von Maruyama et al durch Anwendung der Oktantenregel auf 7‐Oxo‐GC‐10‐monomethylether und ein weiteres Keto‐Derivat bestimmt 59. Okabe et al setzten GA ( 1 ) mit p ‐Brombenzoylbromid zum 3‐Mono‐ p ‐brombenzoat um und führten eine Kristallstrukturanalyse der erhaltenen prismatischen Kristalle durch 63. Anfänglich bestand eine Unstimmigkeit zwischen den veröffentlichten Strukturen von GB ( 2 ) und GC ( 3 ) bezüglich der Konfiguration der Hydroxygruppe in 1‐Position.…”
Section: Isolierung Und Strukturaufklärungunclassified